Activated Hydrochar Prepared from Longan Fruit (Dimocarpus longan Lour.) Peel via Hydrothermal Carbonization-NaOH Activation for Cationic Dyes Removal - Neza Rahayu Palapa; Alfan Wijaya; Nur Ahmad; Amri Amri; Risfidian Mohadi; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Hydrothermal carbonization is recognized as a method of processing biomass into carbon-rich products due to its energy-saving and environmental-friendly advantages. In this study, two types of hydrochar were prepared from Longan Fruit (Dimocarpus longan Lour.) Peel via hydrothermal carbonization at temperatures of 190°C and 250°C and activated using NaOH (HC-ACT 190 and HC-ACT 250) for removal of malachite green (MG) and rhodamine B (RhB) dyes. The maximum capacity for MG dye removal using HC-ACT 190 and HC-ACT 250 materials was 172.414 mg/g and 250 mg/g, while for RhB dye was 111.111 mg/g and 151.515 mg/g, respectively. The optimum pH was obtained at pH 6 for MG and pH 3 for RhB with adsorption equilibrium time occurring at 90 minutes. The kinetic study shows that the adsorption process follows pseudo-second-order kinetics, while the isotherm model was determined by the Langmuir isotherm model. Materials can be reused effectively for at least 3 cycles with an adsorption percentage of MG dye removal using HC-ACT 190 and HC-ACT 250 materials was 69.91% and 83.15% respectively, while for RhB dye was 35.79% and 55.6% respectively. The material is more selective on MG dye compared to RhB dye based on the selectivity test on the adsorption of the dye mixture.